Предмет: Математика,
автор: nickie
выполнить действия
Ответы
Автор ответа:
0
1) b*(a-b)a*(a-c)*((a-c)*(a+c)(a-b)*(a+b) =b*(a+c)a*(a+b)
2)b-ca+b - b*(a+c)a*(a+b) = a*(b-c)-b*(a-c)a*(a+b) =ab-ac-ab+bca*(a+b)=bc-aca*(a+b) =c*(b-a)a*(a+b)=-c*(a+b)a*(a+b)=-ca
Ответ ---------- (-са)
2)b-ca+b - b*(a+c)a*(a+b) = a*(b-c)-b*(a-c)a*(a+b) =ab-ac-ab+bca*(a+b)=bc-aca*(a+b) =c*(b-a)a*(a+b)=-c*(a+b)a*(a+b)=-ca
Ответ ---------- (-са)
Автор ответа:
0
Решение смотри во вложении:
Приложения:
Похожие вопросы
Предмет: Химия,
автор: petrushka225
Предмет: Геометрия,
автор: silesta11
Предмет: Литература,
автор: zsasa0301
Предмет: Химия,
автор: mag06
Предмет: Биология,
автор: vikabizyukina